2012
DOI: 10.1007/978-1-61779-536-7_1
|View full text |Cite
|
Sign up to set email alerts
|

The Neurotrophin Family of Neurotrophic Factors: An Overview

Abstract: The neurotrophins are a family of closely related proteins that were first identified as survival factors for sympathetic and sensory neurons and have since been shown to control a number of aspects of survival, development, and function of neurons in both the central and peripheral nervous systems. Limiting quantities of neurotrophins during development control the numbers of surviving neurons to ensure a match between neurons and the requirement for a suitable density of target innervation. Biological effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
298
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(308 citation statements)
references
References 86 publications
9
298
0
1
Order By: Relevance
“…Neurotrophins are growth factors primarily described in the development and survival of neural cells (Skaper 2012). The neurotrophin family is composed of nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), neurotrophin 3 (NT-3) and neurotrophin 4 (NT-4).…”
Section: Introductionmentioning
confidence: 99%
“…Neurotrophins are growth factors primarily described in the development and survival of neural cells (Skaper 2012). The neurotrophin family is composed of nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), neurotrophin 3 (NT-3) and neurotrophin 4 (NT-4).…”
Section: Introductionmentioning
confidence: 99%
“…In a number of murine tissues, the development and survival of sympathetic neurons depend upon the presence of target-derived neurotrophins the best characterized of which is nerve growth factor (NGF) in BAT (Nisoli et al, 1996) and WAT (Peeraully et al, 2004). In spite of their function as growth factors primarily for development and survival of neural cells (Skaper, 2012), Chaldakov et al (2010) reported that many neuropeptides, neurotrophic factors and receptors are shared by the brain and adipocytes, hence, proposing adipose tissue as a member of the diffuse neuroendocrine system.…”
mentioning
confidence: 99%
“…Recent studies demonstrated that TrkA expression was increased during the progression of medullary thyroid carcinoma and neuroblastoma (70). domain can be phosphorylated and bind to a number of death-signalling proteins (40,41).…”
Section: Involvement Of Ngf and Trka In Cancer Growthmentioning
confidence: 99%
“…Unlike p75NTR which can be activated by all neurotrophin family members, TrkA is activated only by particular neurotrophins (Figure 1) (40,(42)(43)(44). Like most receptor tyrosine kinases, TrkA is activated by ligand-induced formation of non-covalently associated receptor dimers (43).…”
Section: Involvement Of Ngf and Trka In Cancer Growthmentioning
confidence: 99%